THE IMPACT OF THE AMERICAN SUPREME COURT DECISION OVER CHARACTERIZING DOMAIN NAMES AS A DIGITAL TRADEMARK final draft may 23 - wahdani, Fahed A. fahed (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Given that the internet has actually arisen, new sensations, one of the other traits, have shaped the connection of digital society. The relation between the stakeholders (trademarks' holders and domain names' owners ) has been vividly illustrated much more frequently than certainly not as an uncertain and contradictory connection over potential interests, revenues, and the financial decorum of hallmarks. In the early digitalization change, the worldwide web was considered a double-edged sword in commercial legal, and technical aspects. The colossal contrast between technical and legal aspects has created a deep gap between the conflict's parties over disputed rights. This gab has been incarnated in the existence of unique legal challenges which turned into lasting insomnia in the heads of legislators and legal entities. Among other difficulties, the domain name character was the main challenge. Besides the lack of lawful arranging regulations, the major obstacle to dealing with this dilemma was the unclarity of the lawful character of the domain names, a minimum of at the very early time of cybersquatting existing as a lawful concern. It was thought that apprehending the lawful character of domain names would certainly return the safety of this disorderly relation. Besides, it would give full protection to these rights related to domain name owners and trademark holders on parallel. In this paper, the author will try to give a new vision associated with the legal nature of domain names based on the new court decision agreeing to register the domain name as a trademark.
Keywords: domain names, cyberspace, digital trademark, trademark holders, domain names